NATIONAL CULTURE AND PATERNALISTIC LEADERSHIP: INDONESIAN BUSINESS CONTEXT - Butar Butar, Ivan Destian (Journal of Business And Entrepreneurship, 2018)
Examining the generalizability of leadership theories that are mainly developed in Western countries in different cultural contexts is an important inquiry in the cross-culture leadership field. A study of 198 subordinates in leading telecommunication and banking companies confirms the applicability of paternalistic leadership in Indonesian context. Result also finds that significant differences are not found among participating companies.